An effect of herbal medicine in Busoore Labaniya (acne vulgaris) among MSME employees in Kottigepalya, Bangalore: an open intervention field trial study - Imlaque, Mohd; Husain, Safder; Bibi, Chand; Sherwani, Arish Mohammad Khan (International Journal Of Community Medicine And Public Health, 2025)
Background: Acne vulgaris is a prevalent skin condition characterized by blocked hair follicles, leading to irritation and the formation of comedones (blackheads and whiteheads). Various factors, including hygiene, occupational environment, and stress, can modify acne development. Aggravating factors such as hot climates and stress contribute to worsening acne. The primary objective of the study was to assess the efficacy of herbal medicine using the Cook's grading scale for acne vulgaris. Methods: A study titled "an effect of herbal medicine in Busoore Labaniya (acne vulgaris)" was conducted among MSME workers in Kottigepalya, Bangalore. This open intervention field trial study compared the effects of local herbal application with traditional treatments for acne vulgaris. A total of 63 patients participated, with 50 completing the 30-day protocol involving the local application of an herbal medicine paste, resulting in observable improvements based on the Cook's grading scale. Results: The study included 50 patients aged 18-30 years, with most participants falling in the 18-20 age group. The average age of the participants was 22.7±3.63 years. The prevalence of acne in this age range was consistent with findings from the Global Burden of Disease study. The gender distribution was 52% male and 48% female, the study also highlighted the significance of hygienic practices, with a majority of patients being skilled workers. Conclusions: The present study revealed that intervention of herbal drugs formulation was found safe and very much effective in the treatment of Busoore Labaniya.